Development of a large Danish single-centre retro- and prospective transgender cohort using a web-based platform: a study protocol of a transgender cohort study - Ulrik Schiøler Kesmodel; Allan Stensballe; Emma Elisabeth Skovby Petersen; Frederika Kiy; Michael Winterdahl; Jakob Dal; Maria Lucia Pop; Gry Kjaersdam Telléus; Astrid Ditte Højgaard (BMJ Open)
Introduction Referrals for gender-affirming healthcare services have surged in recent decades, presumably driven by increased visibility, acceptance and reduced barriers to care. Despite these advances, transgender and gender-diverse individuals continue to face significant mental health challenges, including elevated rates of anxiety, depression as well as high prevalence of autistic traits. Gender-affirming hormonal treatment (GAHT) has been suggested to improve mental health and quality of life (QoL) among transgender individuals; however, the short- and long-term treatment effects of GAHT are not yet fully understood. Therefore, this study aims to establish a comprehensive cohort of transgender individuals at the Centre for Gender Identity (CGI), Aalborg University Hospital, Denmark, to enhance understanding and treatment outcomes.Methods and analysis The Transgender Cohort (TraCK) will recruit participants from February 14, 2024, with recruitment occurring continuously alongside yearly follow-up. This single-centre cohort study will include both retrospective and prospective data collection. Transgender individuals referred to CGI will be invited to participate in the study via the Danish digital mail system called e-Boks. Participants must provide informed consent and complete a baseline questionnaire. Data will be collected from self-reported questionnaires and medical records across multiple specialists. Self-reported questionnaires include WHO-Quality of Life BREF, Eating Disorders Examination Questionnaire, Autism Spectrum Quotient, Transgender Congruence Scale, and Gender Minority Stress and Resilience Measure. Medical records will provide information on demographics, mental health, physical health, and gender-affirming treatment details. Data will be managed using REDCap, ensuring compliance with GDPR and the National Data Protection Act.Ethics and dissemination While recognising the potential privacy risks associated with data collection, the study considers these outweighed by the benefits of advancing knowledge on gender diversity and the impacts of gender-affirming care. The North Jutland Region Ethics Committee reviewed the project, determining no formal approval was needed, but it was registered and approved (no. F2024-012) by the North Jutland Region. Findings will be disseminated through peer-reviewed journals, conferences, and accessible reports for participants.Registration details This study is registered with the North Jutland Region (no. F2024-012). Recruitment and data collection began on February 14, 2024, and will continue alongside yearly follow-up. Keywords Transgender individuals, transgender and gender-diverse, transgender cohort, transgender health, transgender research, cohort study, gender-affirming care.